Polyscias scutellaria: An emerging source of natural antioxidants and anti-inflammatory compounds for health - Adi Muradi Muhar; Adrian Joshua Velaro; Arya Tjipta Prananda; Sony Eka Nugraha; Gamze Çamlik; Siddhanshu Wasnik; Satirah Zainal Abidin; Osfar Sjofjan; Muhammad Andika Yudha Harahap; Muhammad Faridz Syahrian; Nurpudji Astuti Taslim; Nelly Mayulu; et al. (Pensoft Publishers, 2023)
Polyscias scutellaria (PS), an increasingly recognized botanical marvel, has emerged as a remarkable reservoir of natural antioxidants and anti-inflammatory compounds, holding immense potential for enhancing health and promoting overall well-being. In this comprehensive investigation, we meticulously examined the multifaceted properties of PS through various parameters, including DPPH scavenging activity, total phenol, and total flavonoid content in its ethanol extract (EEPS), ethyl acetate extract (EAPS), and n-hexane extract (nhPS). Additionally, we conducted in-depth assessments of cellular responses to EEPS and EAPS, encompassing cell viability, nitric oxide (NO) production, and the modulation of pivotal pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), and interleukin-12 (IL-12), utilizing the RAW 264.7 cell line as a model system.Our findings illuminate the exceptional antioxidant prowess of PS extracts, with EEPS, EAPS, and nhPS displaying noteworthy DPPH scavenging activities. These results underscore their potential in quenching harmful free radicals and mitigating oxidative stress. Furthermore, our investigation unveils the promising anti-inflammatory attributes of EEPS and EAPS, as evidenced by their capacity to preserve cellular viability, dampen NO production, and suppress the secretion of critical pro-inflammatory mediators (TNF-α, IL-6, IL-1β, and IL-12) in RAW 264.7 cells. These remarkable anti-inflammatory effects hint at the therapeutic potential of PS in ameliorating chronic inflammatory conditions and bolstering the body's immune response.In conclusion, Polyscias scutellaria stands as an emerging botanical champion, offering a wealth of natural antioxidants and anti-inflammatory compounds that hold great promise for optimizing health and well-being. This study opens exciting avenues for future research to elucidate the precise bioactive constituents within PS and unravel their intricate mechanisms of action, paving the way for the development of innovative therapeutic interventions and wellness-enhancing products. The remarkable properties of PS underscore its potential as a cornerstone of holistic health and a valuable asset in the pursuit of a vibrant and balanced life. Graphical abstract